Improving Junk Sale and Purchase Transactions Using a Spiral Model-Based System - Setyadi, Heribertus Ary; Supriyanta, Supriyanta; Nurohim, Galih Setiawan (Universitas Bina Darma, 2024)
Traditionally, individuals looking to sell junk or recyclable materials often rely on waiting for roaming junk collectors, a process that is inefficient and lacks transparency. Furthermore, the fluctuating prices of junk goods frequently leave sellers uninformed, creating uncertainty in transactions. To address these issues, this research developed a smartphone-accessible system designed to facilitate junk goods transactions. The system was developed using the Spiral Model, ensuring iterative refinement and reliability. Key features of the system include real-time price updates for junk items, enabling customers to stay informed about the latest market values, and a Location-Based Service (LBS) feature that allows customers to share their location with collectors. This feature enhances the efficiency of junk collection by providing real-time location tracking, enabling collectors to locate and reach customers seamlessly. The implementation of this system aims to make junk buying and selling transactions more effective, transparent, and satisfying for customers. The results of this study demonstrate that the developed system significantly streamlines the transaction process, ensuring improved service delivery and customer satisfaction.